Beyond Big Data: the Dual Mediation of Perceived Personalization and Customer Engagement in the Analytics Loyalty Link within Digital Markets - Nuri Purwanto; Amelia Amelia; Nico Irawan (School of Business, IPB University (SB-IPB), 2026)
Background: Digital marketplaces leverage Big Data Analytics (BDA) to understand customer behavior, but the mechanisms by which BDA forms loyalty remain unclear, particularly through personalized perceptions and customer engagement; whereas competition and low switching costs make loyalty difficult to maintain. Purpose: The purpose of this study is to examine the effect of BDA capabilities on customer loyalty and the dual mediating role of perceived personalization (PP) and customer engagement (CE) in the digital marketplace.Design/methodology/approach: A cross-sectional quantitative study on 300 marketplace users in Surabaya (≥17 years; ≥3 transactions/6 months) with purposive sampling. Data were collected via a Likert scale online questionnaire (items adapted from the literature) and analyzed with PLS-SEM (SmartPLS 4.0) and bootstrapping for mediation testsFindings/Result: The results show that the use of big data analytics in digital marketplaces is able to strengthen customer loyalty through two main channels. First, as the platform gets better at processing and utilizing customer data, customers increasingly feel that there are services that suit their personal needs, such as relevant product recommendations, targeted offers, and a shopping experience that feels